PENGARUH INTENSITAS BERMAIN GAME ONLINE DAN PERAN ORANG TUA TERHADAP MINAT BELAJAR PESERTA DIDIK DI SMA NEGERI 3 MANADO - Mayampoh, Timotty; Sumual, Tinneke; Wuisang, Jerry (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2025)
This study aims to determine the effect of the intensity of playing online games and the role of parents on students' interest in learning at SMA Negeri 3 Manado. This study uses a quantitative method by taking a sample of 50 students. The techniques used in data collection are observation, questionnaire techniques (questionnaires) and documentation. The analysis of the instruments used is the validity and reliability test. The data analysis technique used, multiple regression analysis. The results of this study indicate that (1) There is a significant effect of the intensity of playing online games on students' interest in learning at SMA Negeri 3 Manado. (2) There is a significant effect of the role of parents on students' interest in learning at SMA Negeri 3 Manado. (3) There is a significant effect of the intensity of playing online games and the role of parents on students' interest in learning at SMA Negeri 3 Manado.Keywords: Intensity of playing online games, role of parents, interest in learning